Ефективність використання сільськогосподарських земель при виробництві окремих культур - Малярець, Людмила Михайлівна; Ульянченко, Наталія Володимирівна (My University, 2022)
Досліджуються проблеми ефективності використання сільськогосподарських земель при виробництві соняшнику, кукурудзи на зерно та пшениці в підприємствах Харківської області. Метою дослідження є оцінка процесу формування рівня прибутковості виробництва соняшнику, пшениці та кукурудзи на зерно та виділення окремих факторів впливу на її величину. Було встановлено, що між величиною витрат та прибутку не виявлено чітких залежностей. Констатується чітка залежність між величиною урожайності та величиною прибутку на 1 га посівної площі. Побудована регресійна модель залежності величини прибутку на 1 га посівної площі від окремих факторів. Всі побудовані моделі були надійними та мали середній рівень зв’язку. Встановлено від’ємний характер зв’язку між рівнем витрат на 1 га посівної площі та рівнем прибутку. Робиться висновок про чіткий прояв закону спадної віддачі, який характеризує поступове падіння величини прибутку в процес нарощування витрат.

The author investigates problems of the efficient use of agricultural land in the production of sunflower, corn for grain and wheat at the enterprises of Kharkiv region. It is emphasized that the selected crops occupy 85.4% in the structure of the sown area and actually determine the overall field efficiency of crop production. Moreover, to a large extent, they shape the development trend of the entire agriculture. The purpose of the study is to assess the formation process of the profitability level of sunflower, wheat and corn production for grain and to identify individual factors influencing its value. The author applied the grouping, modeling dependencies research methods, using regression analysis. The object of the study is the data of statistical reporting from agricultural enterprises. There was no clear relationship between the amount of expenses and profit. In the case of sunflower production at enterprises that had losses, the expenditure per hectare was on average UAH 18,861, for wheat - UAH 19,121, for corn for grain - UAH 20,047. At a profit level of UAH 15,000.1-20,000/ha, the cost for sunflower was UAH 13,335/ha, wheat - UAH 14,365/ha, corn for grain - UAH 15,520/ha. The author has established the fact that there is a clear relationship between the amount of productivity and the amount of profit per 1 ha of the sown area. It is noted that the largest planted area for sunflower and wheat is at the enterprises with a profit of 15,000.1-20,000 UAH/ha, for corn for grain - with an increase in profit - 5,000.1-10,000 UAH/ha. The smallest sown area for all three crops was at the enterprises that had a loss. The article demonstrates a regression dependence model of the profit amount per 1 ha of sown area on the expenses per 1 ha of the sown area, crop productivity and the production cost of 1 centner of products. All constructed models were reliable and had an average level of communication. The article emphasizes negative nature of the relationship between the expenses per 1 ha of sown area and the level of profit. A conclusion is made about a clear manifestation of the law of diminishing returns which characterizes gradual decrease in the amount of profit in the process of increasing costs. It is emphasized separately that the main factor in the formation of profitability level of crops is the level of their productivity.
Efficient use of agricultural lands in the production of individual crops
Keywords: прибуток; ефективність виробництва; землекористування; виробнича собівартість; інтенсивність виробництва; закон спадної віддачі; profit; production efficiency; land use; production cost; production intensity; law of diminishing returns